Two-dimensional strain field analysis of reinforced concrete D-regions based on distributed optical fibre sensors. (1st March 2023) - Fernandez, Ignasi; Berrocal, Carlos G.; Rempling, Rasmus
Highlights: 2D-strain fields measurements by distributed optic fibre sensing technology in D-regions under loading are presented. The interpolation method proposed enables for the visualization of strain fields on the whole element surface, not only at the measurement points. The proposed fibre optic cable arrangement allows for the calculation of principal strains and shear strain along the element, and its visualization. The strut and tie mechanisms formed in the element as well as the cracking development is well capture by the fibre optic and represented visually represented. Abstract: The introduction of Distributed Optical Fibre Sensing in experimental testing of reinforced concrete structures has enabled the acquisition of measurements with an unparalleled level of detail, providing an accurate and ubiquitous description of cracking and deflections throughout an element. However, most of the available research using this technology has focused on the study of beam specimens and high quality data for the calibration and development of models that can describe accurately the behaviour of D-regions in service is still lacking. For that reason, the application of distributed optical fibre sensing in D-regions remains a subject of interest. In this work a method for the deployment of fibre sensors in a multilayer configuration is presented for a wall element. An interpolation approach is then proposed, which combined with the distributed nature of the sensors enabled the description of detailed heat maps for the global and principal strain fields. The results indicated that shear strains can reveal the position of shear cracks well before they are formed whereas the maximum and minimum principal strains clearly show the crack pattern and crack development as well as the load transfer mechanisms including, for the first time, the experimental identification of a secondary strut-and-tie mechanisms.